Assessment of self-care in heart failure patients at a cardiac hospice in Peshawar, Pakistan. - Khan , Awal; Dildar Muhammad; Khan , Afsha; Dewey , Rebecca Susan (International Journal of Endorsing Health Science Research, 2022)
Background: The significance of self-care in heart failure is yet to be demonstrated empirically; however, it's commonly believed that effective self-care delays the development of heart failure. This study aimed to assess the level of self-care among patients with heart failure attending a cardiac hospice center in Peshawar, Pakistan. Methodology: A cross-sectional study design was used to examine self-care maintenance, self-care management, and self-care confidence in heart failure patients at Heart Hospice Center, Hayat Abad Medical Complex. A total of 195 heart failure patients were recruited using a convenient sampling method. Data were collected using the Self Care Heart Failure Index (SCHFI) version 6.2. Results: The mean SCHFI score (comprising 22 items) across n=195 participants was 50 ± 28.9. A very low percentage (31.28%, n=61) scored an accepted level (≥70) of self-care. On the subscales of self-management, self-confidence, and self-maintenance, the mean scores were 50.0 ± 28.8, 46±26.6, and 50.0 ± 28.7, respectively. One hundred eighty symptomatic patients completed the self-care management subscale who was experiencing shortness of breath and ankle swelling. Conclusion: Heart failure patients attending the Heart Hospice Center in Peshawar, Pakistan, did not portray a satisfactory level of self-care behavior. More effective nursing interventions are needed to manage heart failure patients in this center.